Dinamika Perlindungan Hukum Pekerja Remote Working Melalui Implikasi Digital dan Pengaturan Di Indonesia - Devina Novela (Journal of Mandalika Literature, 2024)
Technological advances in the world of work have led to various kinds of renewal systems, one of which is the Remote Working system that does work remotely. With the existence of this system brings enormous changes, of course, in the dynamics of the system by Remote Working companies. In this study there are two problem formulations, namely the implications of the development of digital technology on the working relationship between Remote Working workers and companies in Indonesia, the dynamics of legal protection of Remote Working workers through digital implications and arrangements in Indonesia. With normative juridical research methods that examine using library materials or secondary data. In essence, this study aims to explain the dynamics of technological developments that trigger positive and negative impacts on the relationship between companies and remote working workers. Then legal protection for Remote Working workers can be seen from the Manpower Law, Ciptaker Law, and PDP Law.